Vanishing point - Muller, Marcia (Muller, Marcia. Sharon McCone mysteries., 2006)
"Sharon McCone is hired to investigate the 22-year-old cold-case of a housewife and artist who vanished inexplicably in the central part of California"--Provided by publisher.